Partial Least Squares Structural Squation Modeling (PLS-SEM) Analysis for Social and Management Research : A Literature Review - Purwanto, Agus; Sudargini, Yuli (Journal of Industrial Engineering & Management Research, 2021)
Many social and management studies use quantitative methods that use partial least sound. The purpose of this article is to explain the sequence and standard of data processing using partial least squares for social and management research. The method of writing this article is to review articles written by Hair. The results of the explanation of this article can help researchers to process and analyze data with partial least squares. PLS is an acronym for Partial Least Square. Broadly speaking, PLS is a measuring tool in statistical methods. PLS is a multivariate technique that is capable of managing various things such as response variables to explanatory variables simultaneously. From the initial explanation, it is clear how PLS brings convenience to those who master it.Actually, PLS is an alternative in statistics